Nexus between Returns on Equity and Disclosures of Greenhouse Gas Emissions, Waste Management, and Renewable Energy - Emmanuel, Yinka Lydia; Owolabi, Oluwasikemi Janet; Owolabi, Babatunde Ayodeji; Kwarbai, Jerry D.; Akinbode, James Olalekan; Olasupo, Sunday Festus; Kolawole, Isiaka Olayinka; Otekunrin, Adegbola Olubukola (International Journal of Energy Economics and Policy, 2024)
Environmental sustainability is now being continuously researched in almost all areas of humankind. This study investigated the impact of environmental sustainability disclosures (proxy by renewable energy disclosures, Greenhouse Gas Emissions disclosures, and waste management disclosures) on the returns on equity of sampled Quoted Nigerian Financial Institutions. Purposely, Fourteen Quoted Nigerian Financial Institutions on the Nigerian Exchange Group were taken as the sample size for this study. The study spanned a period of 9 years from 2013 to 2021. The analysis was carried out using panel data and employing multiple regression models to assess the relationships between the variables using secondary data collated from the annual reports of Quoted Nigerian Financial Institutions. The findings of the study reveal that the impact of renewable energy disclosures (with coefficient estimate = -0.19295, t-value = -1.41 and p-value = 0.16), Greenhouse Gas Emissions disclosures (with coefficient estimate = -0.16105 & the t-value = -1.18 p-value = 0.239, and waste management disclosures (with coefficient estimate = 0.124013, the t-value of 1 and p-value = 0.317) on returns on equity is not significant. This study concluded that the relationship between return on equity and environmental sustainability variables disclosures (proxy by Renewable Energy Disclosure and Greenhouse Gas Emissions) is unrelated.